2022
DOI: 10.1007/s00431-022-04387-x
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of child abuse with subdural hemorrhage during the first year of the COVID-19 pandemic: a nationwide study in France

Abstract: The global COVID-19 pandemic prompted governments to impose unprecedented sanitary measures, such as social distancing, curfews, and lockdowns. In France and other countries, the first COVID-19 lockdown raised concerns about an increased risk of child abuse. Abusive head trauma (AHT) is one of the most serious forms of child abuse in children aged 0–24 months and constitutes the leading cause of death in children under 2 years of age. Subdural hemorrhage (SDH) is present in 89% of cases of AHT and constitutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…In an analysis of the U.S. based PHIS database during the first six months of the pandemic, Maassel et al found no change in mortality for AHT patients compared to the three prior years ( Maassel et al, 2021 ). Similarly, Caron et al, who analyzed a nationwide French database, found no change in mortality among children 0–24 months old admitted for abusive subdural hemorrhage in the first 12 months of the COVID-19 pandemic compared to the two prior years ( Caron et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an analysis of the U.S. based PHIS database during the first six months of the pandemic, Maassel et al found no change in mortality for AHT patients compared to the three prior years ( Maassel et al, 2021 ). Similarly, Caron et al, who analyzed a nationwide French database, found no change in mortality among children 0–24 months old admitted for abusive subdural hemorrhage in the first 12 months of the COVID-19 pandemic compared to the two prior years ( Caron et al, 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…Intriguingly, an additional analysis of the same PHIS database by another group reported increased odds of AHT during the first three months of the pandemic ( De Boer et al, 2022 ). A review of the French national hospital registry reported a similar incidence of hospital admissions for subdural hemorrhages and mortality in the context of child abuse during the first year of the pandemic compared to the two prior years ( Caron et al, 2022 ). The authors of these four database studies recognize the limitations of their methodology, including reliance on International Classification of Diseases (ICD) codes, reliance on limited recorded data, and absence of case-specific information.…”
Section: Introductionmentioning
confidence: 99%
“…Increased traumatic injuries were described during the first month after the closure of childcare facilities in an American pediatric trauma center ( Kovler et al, 2021 ), or AHT during the first month of the national lockdown in the United Kingdom ( Sidpra, Abomeli, Hameed, Baker, & Mankad, 2021 ). However, in France, no significant increase in children with subdural hematoma was observed during the first year of the pandemic compared with the two previous years ( Caron et al, 2022 ). But an important increase of the incidence and the severity of AHT was observed in the single regional pediatric neurosurgery center in Paris during the first two years of the pandemic ( Lãzãrescu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
“…Reports from other sources are mixed; violence and abuse hotlines note general increases in call volume ( De Boer et al, 2021 ; Loiseau et al, 2021 ; Petrowski et al, 2021 ; Rapoport et al, 2021 ), whereas emergency department records show more variation with reports of no changes ( Caron et al, 2022b ; Chaiyachati et al, 2022 ; Russell et al, 2020 ), decreases ( Bullinger et al, 2021b ; Chaiyachati et al, 2022 ; Stivaros et al, 2022 ;), as well as increases in both cases ( Amick et al, 2022 ; Bullinger et al, 2021c ; DeLaroche et al, 2021 ; Kovler et al, 2021 ; Loiseau et al, 2021 ; Sidpra et al, 2021 ), and severity of abuse ( De Boer et al, 2021 ). Several studies have also demonstrated a change in the distribution of types of CM, including dramatic increases in admissions related to neglect or lack of supervision ( Bullinger et al, 2021b ), and admissions related to pediatric abusive head trauma since the pandemic onset ( Sidpra et al, 2021 ).…”
Section: During the Covid-19 Pandemicmentioning
confidence: 99%